APLIKASI KASIR BERBASIS WEB UNTUK UMKM BAKARIN ROTI - kennedy, janero (Jurnal Teknologi dan Bisnis, 2021)
The research was conducted to find out the cashier services for UMKM Bakarin Roti which were still done manually when inputting data, causing customer queues to pile up. In addition, the manual system has many weaknesses, including most errors in recording, and data search which is difficult because every time a seller’s data is searched, he must search the ledger. There is no specific information that informs about the amount of stock, so it is not uncommon when the stock runs out, the shop owner will only know when a transaction process has taken place, thus disappointing the customer. Given these weaknesses, we need a web-based cashier application that can facilitate cashier data management. The method used is waterfall, in making applications starting from the analysis, design, coding, testing, evaluation, and maintenance stages.